Use of telehealth for measurement of anthropometrics in toddlers and their parents - Sarah S. Farabi; Sarah S. Farabi; Cindy Schwarz; Bria Lee-Robinson; Lauren G. Fiechtner; Victor Davila-Roman; Rachel G. Tabak; Debra Haire-Joshu (Frontiers in Digital Health, 2025)
IntroductionThe use of telehealth (e.g., live video calling) to collect anthropometric data in toddlers and their parents to increase participation in lifestyle interventions holds promise. But, there is limited evidence to support reliability of telehealth for the collection of these measures. This study aimed to determine the reliability of use of telehealth with parents to collect anthropometric and blood pressure measures on themselves and anthropometric measures on their toddler and determine the acceptability of instruction.MethodsThis cross-sectional study was conducted as part of the developmental phase of a larger study. Research staff instructed parents via video call to measure their own and their toddler's anthropometrics, and their own blood pressure. Next, research staff collected the same measurements in-person. Intraclass Correlation Coefficients (ICC), relative technical error of measurement (TEM) and reliability coefficient values were computed.ResultsThirty-seven parent/toddler dyads were enrolled in the study. ICC values for parent vs. research staff measured parental height and weight were 0.98 and 0.99, respectively, and relative TEM values were 0.44% and 0.14%, respectively. ICC values for parent vs. research staff measured toddler height and weight were 0.98 and 0.99, and relative TEM values were 1.60% and 0.82%, respectively. ICC values for parent vs. research measured systolic and diastolic blood pressure were 0.86 and 0.89 respectively.DiscussionParental self-measurement of height, weight, and blood pressure, and measurement of toddler height and weight is reliable and acceptable to parents when performed using telehealth.